Enhancing Growth and Macronutrient Efficiency Through Rainfed Fertigation in Greenhouse Hydroponic Leafy Vegetables - Sudirman Sirait; Herry Suhardiyanto; Satyanto Krido Saptomo; Liyantono (Bogor Agricultural University, Indonesia, 2026)
Reliability of hydroponic crop cultivation in greenhouses requires sustainable management of nutrients and water. Nutrient supply based on rainwater harvesting is a viable strategic practice for crop cultivation systems. However, further exploration of the effects on physiological responses and crop yields across various nutrient concentrations is important to improve usage efficiency. This study examined the impact of macronutrient deficiencies on the growth and yield of leafy vegetables using a rainwater-harvesting. Rainwater harvested from the greenhouse roof was fully utilized as a water source for the nutrient solution applied to the plants. Pak choi (Brassica rapa var. chinensis) and lettuce (Lactuca sativa L. var. crispa) were cultivated hydroponically using the Nutrient Film Technique system under varying macronutrient concentrations (25, 50, 75, and 100%) based on a modified Hoagland standard solution. Additional treatment was applied as a macronutrient deficiency, adjusted to the macronutrient content of the harvested rainwater. The number of leaves, SPAD index, fresh weight, and nutrient status were measured for each treatment every three days after planting until harvest. Pak choi plants showed greater tolerance to low levels of macronutrient deficiency, whereas lettuce was only tolerant of low levels of potassium deficiency. Rainwater-based nutrient supply maintained the growth and yield of leafy vegetables without a significant difference compared to the control, while reducing macronutrient inputs by 0.21-24.02%. These results indicate that macronutrient concentrations can be lowered to enhance fertilizer use efficiency and prioritize economic benefits.